UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA DI MADRASAH IBTIDAIYAH NURUN 2 RENGAS CIPUTAT TANGERANG SELATAN MELALUI KEGIATAN PARTISIPATORY - Gelar Dwirahayu; Femmy Diwidian (Study Program of Mathematics Education of Unimed Postgraduate Program, 2014)
The four of competencies for the teacher and lecturers according to Education Law in Republic Indonesia Number 14 year 2005 are pedagogical competence, personal competence, social competence and professional competence. Professional and pedagogical competence skills related to teacher or lecture ability on manage learning process in the classroom to improve learning outcomes particularly on mathematics. Most of the teachers face many obstacles to improve the pedagogical and professional competence, one of the reason is infrequently on seminar or workhsops. The effort that can help teacher to improve the pedagogical and professional competence is through cooperation between university and school which is called participatory action research, this partnership aims to (1) Implementing the theory of mathematics’ teaching and learning in the class; (2) Assist the teacher to arrange lesson plan in mathematics; (3) Develop innovative strategi, model or approach for mathematics’ teaching and learning; and (4) Conducting relationship between university and stakeholders, in this case islamic primary school/Madrasah. The result showed that the activities of participatory action research in islamic primary school Nurun Najah 2 Rengas Chester positive impact on mathematics learning activities, particularly increasing students' understanding in cognitive, affective and psychomotor aspect.